Implication of allergy and atopy in IgG4-related disease - Katherine D’Astous-Gauthier, MD; Mikael Ebbo, MD, PhD; Pascal Chanez, MD, PhD; Nicolas Schleinitz, MD, PhD (World Allergy Organization Journal, 2023)
Immunoglobulin G4-related disease (IgG4-RD) is a chronic multi-organic immune fibrosing disease. It affects preferentially men around middle age and almost any organs can be involved; however, lymph nodes, submandibular and lacrimal glands, pancreas, and retroperitoneum are the most affected. The mainstay treatment is corticosteroids, sometimes adjuncts with DMARDs or rituximab as steroid sparing agents. Th2 inflammation is implicated in the pathophysiology of the disease. Several reports indicate that allergy and/or atopy often affect patients with IgG4-RD. The frequency varies greatly between studies with allergies/allergic diseases reported in 18–76% while atopy is reported in 14–46%. In studies including both, they affect 42 and 62% of patients. Rhinitis and asthma are the most frequent allergic diseases. IgE and blood eosinophiles are often elevated and few studies report that basophils and mast cells could participate in the disease pathogenesis; however, the implication of allergy and atopy remain unclear. No common allergen has been identified and IgG4 production seems to be polyclonal. Although a direct causal effect is unlikely, they could potentially shape the clinical phenotype. Allergies/allergic diseases and/or atopy are reported to be more frequent in IgG4-RD patients presenting head, neck, and thoracic involvement, with higher IgE and eosinophils and less frequent in retroperitoneal fibrosis; however, studies regarding allergy and atopy in IgG4-RD are highly heterogenous. The aim of this article is to review what is currently known about the allergy and atopy in the context of Ig4-RD.